INTERNAL CONTROL: AN ANALYSIS OF THE PERCEPTION OF THE PURCHASING CENTER OF A STATE GOVERNMENT ACCORDING TO THE COSO FRAMEWORK - Matos, Gabriele Bernardelli de; Oliveira Pereira da Silva, Maria Daniella de; Almeida, Karla Katiuscia Nóbrega (Management Control Review, 2022)
The internal control systems in public agencies are fundamental instruments for the management of work environments, processes, and risks to which these structures are exposed. Thus, the present work aimed to evaluate the perception of the public servants of the Purchasing Center of a state government regarding the level of adherence to the components of internal control based on the COSO ERM framework. The research was characterized as a case study, in which data collection took place through the application of a questionnaire, structured to the components of COSO ERM, along with a sample of public servants from the Purchase Center, as well as a semi-structured interview with the executive director and participant observation was used to have a more critical view of the perception of those observed. The main results showed a uniform perception of the participants regarding the governance and culture component while the differences found were directed to the performance component, both results report the absence of well-defined governance structures and the inconsistency of information between the public servants. Despite this, the internal control practices carried out in the Purchasing Center, according to the perception of the interviewed groups, present higher levels of adherence to the components of strategy and definition of objectives and review, a result that evidenced the commitment of the Purchasing Center with the strategic planning and monitoring of its activities.